Recent innovations and challenges in the treatment of fungal infections - Liu, Di; Zhou, Renjie; Gao, Xindi (Frontiers in Cellular and Infection Microbiology, 2025)
The prevalence of fungal infections has been increasing consistently in recent years, particularly among immunocompromised individuals, resulting in increased mortality. The World Health Organization (WHO) now lists “super fungi”, such as Candida auris as global public health threats, highlighting the urgent requirement for new antifungal therapies. Although conventional agents such as azoles and polyenes remain prevalent in medical treatment, challenges including drug resistance, limited selectivity, and high toxicity limit their value, prompting the need for the development of more effective therapeutic strategies. Current research trends are shifting towards multi-mechanistic combination therapies and biotechnology-driven approaches, which demonstrate significant potential. This review summarizes recent advances and outlines directions for future antifungal drug development and new therapies.